The Relationship Between Affective Disorders, Preoperative Pain Interference, and PROMIS-29 Quality Domains in the Spine Population: A Retrospective Review. (16th November 2020) - Christian, Zachary; Afuwape, Olusoji A; Aoun, Salah G; Bagley, Carlos A; Hall, Kristen
Abstract: INTRODUCTION: Previous research has demonstrated that patients with established affective disorders are associated with increased post-operative pain and readmission rates. Despite these findings, questions remain regarding the significance of pre-surgical ratings of pain on the clinical status and recovery of spine surgery patients. METHODS: The records of 83 consecutive adult patients who underwent elective spinal surgery between January 2016 and August 2017 at a single institution were reviewed. Primary outcomes included the ratings of anxiety, depression, Pain Interference and Pain Intensity pre- and post-operatively, using the PROMIS-29, and post-operative complications in patients with AD (depression, anxiety, Post Traumatic Stress Disorder, Obsessive Compulsive disorder, panic disorder, and bipolar disorder) compared to controls. RESULTS: Patients with affective disorders had higher ratings of pain interference preoperatively ( P = .020) and 3 months ( P = .011) and 12 months ( P = .004) postoperatively as well. AD patients with elevated pre-operative Pain Interference scores (>14) also had higher postoperative ratings of Pain Intensity ( P = .0004), depression ( P < .0001) and anxiety ( P < .0001) compared to AD patients with lower pain levels. Controls with elevated pre-operative Pain Interference scores (>14) also had higher preoperative ratings of Pain Intensity ( P < .001). AD patients in the high pain cohort made phone calls to their clinic provider. Pain Interference levels did not correlate with rates of postoperative complications. CONCLUSION: These findings demonstrate a close relationship between pain, anxiety, and depression, not only in the postoperative setting, but also before surgery in patients with affective disorder diagnoses. In addition, AD patients with higher levels of pain interference also had more patients who made preoperative phone calls to clinic providers, a sign of increased resource utilization when compared to controls with higher ratings of pain interference.